2021
DOI: 10.3390/jmse9121390
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Wave-Dependent Sea Spray Parameterizations on Air–Sea–Wave Coupled Modeling under an Idealized Tropical Cyclone

Abstract: While sea spray can significantly impact air–sea heat fluxes, the effect of spray produced by the interaction of wind and waves is not explicitly addressed in current operational numerical models. In the present work, the thermal effects of the sea spray were investigated for an idealized tropical cyclone (TC) through the implementation of different sea spray models into a coupled air–sea–wave numerical system. Wave-Reynolds-dependent and wave-steepness-dependent sea spray models were applied to test the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Andreas and Emanuel (2001) implemented sea spray-mediated heat flux and momentum flux parameterizations into a simple tropical cyclone model, and found that the sea spray-induced heat flux significantly enhances the tropical cyclone intensity, offsetting the negative effect of enhanced surface drag by strong wind and waves. The similar enhancement of tropical cyclone intensity was also shown in recent regional coupling systems by including sea spray-mediated heat flux (Xu et al, 2021a;Liu et al, 2012;Garg et al, 2018;Zhao et al, 2017). In the First Institute of Oceanography Earth System Model, Bao et al (2020) first incorporated the sea spray-mediated heat flux in global climate simulation.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Andreas and Emanuel (2001) implemented sea spray-mediated heat flux and momentum flux parameterizations into a simple tropical cyclone model, and found that the sea spray-induced heat flux significantly enhances the tropical cyclone intensity, offsetting the negative effect of enhanced surface drag by strong wind and waves. The similar enhancement of tropical cyclone intensity was also shown in recent regional coupling systems by including sea spray-mediated heat flux (Xu et al, 2021a;Liu et al, 2012;Garg et al, 2018;Zhao et al, 2017). In the First Institute of Oceanography Earth System Model, Bao et al (2020) first incorporated the sea spray-mediated heat flux in global climate simulation.…”
Section: Introductionsupporting
confidence: 76%
“…A5-A6 of Appendix A), therefore it is difficult to apply A92 directly in coupled modeling systems. A15 (Andreas et al, 2015) developed a fast algorithm by using a single representative droplet radius (details in Appendix B), which was widely adopted in recent reginal and global coupling systems (Xu et al, 2021a;Liu et al, 2012;Garg et al, 2018;Zhao et al, 2017;Song et al, 2022;Bao et al, 2020). In this study, we apply a 3-node GQ method (details in Appendix C) to develop a new fast algorithm to approximate the full-size spectral integral of A92.…”
Section: Development Of a Fast Algorithm Based On Gqmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a condition unfavorable for sea spray generation, because of the reduction of both wind forcing and wave breaking (Xu et al 2021a). Thus, it has negative feedback on intensification for a larger TC since an increase in sea spray is known to increase the sea-air enthalpy transfer (Andreas and Emanuel 2001;Bao et al 2011;Wang et al 2001;Xu et al 2021b). Second, increased significant wave height and wavelength enhances the TC-induced sea-surface cooling (Fig.…”
Section: Roles Of Ocean Wavesmentioning
confidence: 99%
“…One of the primary reasons is the lack of sufficient understanding of the basic physical mechanisms that generate, drive, and maintain TCs (Chan, 2005; Chan & Kepert, 2010; Elsner et al., 2008). In particular, one external physical process that might affect the intensity of a TC is sea spray (Andreas & Emanuel, 2001; Gall et al., 2008; Xu, Voermans, Liu, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%